2015
DOI: 10.1016/j.acvd.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers of acute decompensated heart failure: The emerging roles of cardiac biomarkers and prognostic scores

Abstract: Rapidly assessing outcome in patients with acute decompensated heart failure is important but prognostic factors may differ from those used routinely for stable chronic heart failure. Multiple plasma biomarkers, besides the classic natriuretic peptides, have recently emerged as potential prognosticators. Furthermore, prognostic scores that combine clinical and biochemical data may also be useful. However, compared with the scores used in chronic heart failure, scores for acute decompensated heart failure have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 68 publications
0
31
0
1
Order By: Relevance
“…However, the majority of included studies examined chronic HF, with only 4 out of 23 papers relating to AHF, although patients with AHF constituted approximately half of the cohort. Furthermore, the burden of HF has shifted over the recent years from CHF to AHF, for which effective and time-sensitive outcome predictors are urgently needed 14. This AHF-specific analysis on the utility of CA125 will complement well with Zhuang et al 15 to provide a holistic picture of CA125 as a prognostic marker for CHF as well as AHF.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the majority of included studies examined chronic HF, with only 4 out of 23 papers relating to AHF, although patients with AHF constituted approximately half of the cohort. Furthermore, the burden of HF has shifted over the recent years from CHF to AHF, for which effective and time-sensitive outcome predictors are urgently needed 14. This AHF-specific analysis on the utility of CA125 will complement well with Zhuang et al 15 to provide a holistic picture of CA125 as a prognostic marker for CHF as well as AHF.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the effectiveness of some of the prognostic markers, the difficulty remains in obtaining determinable predictors in a short time frame for patients with AHF 14. Furthermore, a meta-analysis has been published on the prognostic value of CA125 in HF,15 but only 4 of the 23 included studies concerned patients with AHF.…”
Section: Introductionmentioning
confidence: 99%
“…I n many different areas of cardiovascular physiology [1], cardiac biomarkers have been shown to be very useful tools in evaluating cardiac (dys)function [2], assessing diagnosis [3,4], guiding subsequent management [5], stratifying prognosis [6], as well as assessing total cardiovascular risk [7]. Moreover, they significantly contribute to our knowledge of mechanisms of disease genesis and progression.…”
mentioning
confidence: 99%
“…Age, brain natriuretic peptide, and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels have been shown to correlate with postdischarge rates of readmission and mortality. 5 A study evaluating the prognostic value of a bedside inferior vena cava (IVC) ultrasound exam demonstrated that lack of improvement in IVC distention from admission to discharge was associated with higher 30-day readmission rates. 6 Two studies using data from comprehensive transthoracic echocardiograms in heart failure patients demonstrated that a dilated, noncollapsible IVC is associated with higher risk of mortality; however, it is well recognized that obtaining comprehensive transthoracic echocardiograms in all patients hospitalized with heart failure is neither cost-effective nor practical.…”
Section: Resultsmentioning
confidence: 99%